Pengaruh Sosial Media Marketing, Kualitas Produk, dan Brand Image terhadap Keputusan Pembelian Konsumen di Curlybcoffe Denpasar - Helmi Fauzi Kurnia Saputra; Kadek Adyatna Wedananta (Pusat Riset dan Inovasi Nasional, 2026)
The growth of coffee shop businesses in Denpasar City has intensified competition, requiring business owners to optimize marketing strategies, maintain product quality, and strengthen brand image. This study aims to analyze the influence of social media marketing, product quality, and brand image on consumer purchasing decisions at Curlybcoffe Denpasar. A quantitative approach was used, employing a survey method involving 100 respondents who had made purchases at Curlybcoffe. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that all research instruments are valid and reliable. Partially, product quality and brand image have a positive and significant effect on purchasing decisions, while social media marketing does not show a significant effect. Simultaneously, social media marketing, product quality, and brand image collectively have a positive influence on consumer purchasing decisions at Curlybcoffe Denpasar. These findings show that consumer decisions are more strongly driven by perceptions of product quality and brand image than by promotional content on social media. Therefore, Curlybcoffe should prioritize improving menu quality and strengthening brand identity, supported by a more consistent and engaging social media marketing strategy.